2012
DOI: 10.2134/jeq2012.0014
|View full text |Cite
|
Sign up to set email alerts
|

Occurrence of Ciprofloxacin, Enrofloxacin, and Florfenicol in Animal Wastewater and Water Resources

Abstract: Antimicrobial agent residues are becoming an intractable environmental problem in soil, surface, and underground water. To obtain a broad profile of residues in animal wastewater and surface water, 24 animal wastewater, 8 animal farm effluent, 18 river water, and 8 pond water samples taken in Jiangsu in eastern China were monitored for enrofloxacin, ciprofloxacin, and florfenicol using solid phase extraction and high performance liquid chromatography/electrospray ionization-tandem mass spectrometry (HPLC/ESI-M… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
40
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 108 publications
(42 citation statements)
references
References 53 publications
2
40
0
Order By: Relevance
“…Given the large number of studies presented in literature, our study focused itself on those which were the most relevant to Chinese aquatic environments. Literatures which failed to report details of occurrence data [21,[40][41][42][43][44] and/or geographical information [45][46][47][48][49][50][51] were excluded.…”
Section: Data Collection Strategiesmentioning
confidence: 99%
“…Given the large number of studies presented in literature, our study focused itself on those which were the most relevant to Chinese aquatic environments. Literatures which failed to report details of occurrence data [21,[40][41][42][43][44] and/or geographical information [45][46][47][48][49][50][51] were excluded.…”
Section: Data Collection Strategiesmentioning
confidence: 99%
“…Since their introduction, medical antibiotic use has increased dramatically in the USA with a particular increase in the use of broad spectrum antibiotics in recent years 1. In addition, low-dose antibiotics have been used for agricultural purposes for >50 years,2 leading a nearly ubiquitous exposure to low levels of antibiotics in food and water for individuals who are not receiving antibiotic therapy for therapeutic purposes3 4 Epidemiological studies suggest that this increasing exposure to antibiotics is associated with an increased risk for developing inflammatory diseases including autoimmune disease, inflammatory bowel disease, coeliac disease, food allergy, asthma and obesity 5–11. The spectrum and number of inflammatory disorders associated with antibiotic use and the association of these disorders with a variety of antibiotics suggests that this increased risk is not due to side effects of specific antibiotics, but rather a shared effect across multiple antibiotics impacting a risk for general inflammatory responses.…”
Section: Introductionmentioning
confidence: 99%
“…The acute toxicity test showed that the survival of earthworms was not affected by EF residues in soil because the LC 50 at day 14 which is a standard value for acute toxicity test of earthworms [14] is greatly larger than the environmentally relevant concentration of EF residues [24]. The 48-h acute toxicity test of EF also showed the survival of earthworms was not affected by the low concentration of EF (below 0.634 mg cm À2 ) both on filter paper and in solution, while the morphology changes of earthworms with increasing EF concentrations were observed [22].…”
Section: Discussionmentioning
confidence: 99%